2014
DOI: 10.1093/jnci/dju238
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention With Nuts

Abstract: It is well established that increased nut consumption is associated with a reduced risk of major chronic diseases, such as cardiovascular disease and type 2 diabetes mellitus. On the other hand, the association between nut consumption and cancer mortality is less clear. Recent studies have suggested that nut consumption is associated with reduced cancer mortality. This evidence reinforces the interest to investigate the chemopreventive properties of nuts, and it raises questions about the specific cancer type(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 101 publications
0
43
0
Order By: Relevance
“…Nuts contain a large variety of beneficial bioactive components, including monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) and contain only low amounts of saturated fatty acids (SFA), as well as a number of phytochemicals (i.e., phenolic antioxidants), dietary fiber, and minerals (9,10). PUFAs, including omega-3 fatty acids, reduce inflammation and have also been shown to lower polyp burden in animal models of colon cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Nuts contain a large variety of beneficial bioactive components, including monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) and contain only low amounts of saturated fatty acids (SFA), as well as a number of phytochemicals (i.e., phenolic antioxidants), dietary fiber, and minerals (9,10). PUFAs, including omega-3 fatty acids, reduce inflammation and have also been shown to lower polyp burden in animal models of colon cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Nuts are rich sources of vitamins (e.g., B6, B9, and E), minerals (e.g., selenium and magnesium), fiber, proteins, mono-and polyunsaturated fatty acids, phytosterols, and polyphenols [e.g., flavonoids (quercetin, genistein), stilbenes (resveratrol), and ellagic acid] [5,6]. However, the nutrient composition varies between nut types.…”
Section: Discussionmentioning
confidence: 99%
“…Peanut butter contains the beneficial components of peanuts, although some additives are supplemented to enhance its quality, taste, and presentation [32]. The main proposed mechanisms by which nuts might conduct their cancer-chemopreventive effects relate to their antioxidant and anti-inflammatory effects [5,6]. Other hypothesized mechanisms are the regulation of cell differentiation, proliferation and apoptosis, inhibition of tumor initiation, modulation of angiogenesis, induction of DNA damage repair and detoxifying metabolic enzymes, modification of hormonal mechanisms, and alteration of lipid profiles and cell metabolism [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the effects of dietary fiber on intestinal health have shown that fermentation end products of dietary fiber may contribute to potential chemopreventive effects [11,12]. Fibers are almost indigestible and are fermented by the intestinal microbiota to shortchain fatty acids (SCFA), including butyrate which is particularly effective in chemoprevention.…”
Section: Introductionmentioning
confidence: 99%